Implementing e-Learning–Based Science Media for Straight Motion at the Junior-High Level: A Literature-Based Review - Nurul Fitriyani; Amalia Chairunissa; Alfira Sofia Rahayu (Yayasan Darussalam Bengkulu, 2023)
This study reviews how e-learning media can be designed to support junior-high students’ understanding of straight motion (kinematics) in science classes. Using a narrative literature review, we searched scholarly sources on lower-secondary physics and online/blended instruction, emphasizing 2018–2022 publications and Indonesian implementations during and after the COVID-19 shift; inclusion required relevance to straight motion (e.g., motion graphs, constant velocity/acceleration), explicit use of e-learning platforms or digital resources (e.g., Zoom/Meet, Google Classroom/WhatsApp, Quizizz/Kahoot!, simulations/visualizations), and reportable classroom practices or outcomes. Evidence was extracted on context, platforms, activity structures, representational foci, and reported affordances/constraints, then synthesized thematically. The findings indicate that sequences are most effective when pedagogy not platform novelty drives design: brief multimodal explanations interleaved with questioning and peer talk, layered visuals that explicitly link narratives of motion to position–time, velocity–time, and acceleration–time graphs, and frequent low-stakes retrieval to surface misconceptions about slopes, areas, units, and terminology. Videoconferencing is beneficial when used for short, dialogic segments rather than prolonged lectures; game-based quizzing improves engagement and provides rapid diagnostic feedback; and visualizations/simulations help reduce representational load. Effectiveness is conditional on access and structure, with bandwidth/device constraints and limited oversight of hands-on work as recurrent barriers. This review contributes topic-specific, context-aware design heuristics for straight motion at the junior-high level. Implications include adopting lightweight, bandwidth-resilient “explain–check–discuss” playbooks; curating shared banks of visuals and formative items focused on motion-graph interpretation; providing teacher professional development on discourse moves that elevate student voice; and prioritizing equity-minded participation monitoring to guide iterative improvement.